An Overview of the Constructivist Theories and Their Possible Implications in the Design of the ESP Digital Learning Environment - Živković, Slađana (European Journal of Multidisciplinary Studies, 2016)
This paper provides a brief overview of the constructivist learning theories and explains their significance in the design of the ESP digital learning environment. Constructivism provides a unique and challenging learning environment, and coupled with modern technology shows the potential for great advancement in learning practices. Together they provide the opportunity for new possibilities in the learning process. In other words, they allow ESP students to learn to their fullest potential.Complete understanding of ESP needs an increasing research input, including social interaction and intercultural communication competence. The purpose of ESP is to prepare a student (future specialist) to communicate effectively in the professional field and real-life situations. The ultimate goal is to become operational in any learning situation.